The dream hotel eaudiobook A read with jenna pick: a novel. - Lalami, Laila (Books on Tape, 2025)
READ WITH JENNA BOOK CLUB PICK AS FEATURED ON TODAY ● From Laila Lalami—the Pulitzer Prize and National Book Award finalist and a “maestra of literary fiction” (NPR)—comes a riveting and utterly original novel about one woman’s fight for freedom, set in a near future where even dreams are under surveillance. Sara has just landed at LAX, returning home from a conference abroad, when agents from the Risk Assessment Administration pull her aside and inform her that she will soon commit a crime. Using data from her dreams, the RAA’s algorithm has determined that she is at imminent risk of harming the person she loves most: her husband. For his safety, she must be kept under observation for twenty-one days. The agents transfer Sara to a retention center, where she is held with other dreamers, all of them women trying to prove their innocence from different crimes. With every deviation from the strict and ever-shifting rules of the facility, their stay is extended. Months pass and Sara seems no closer to release. Then one day, a new resident arrives, disrupting the order of the facility and leading Sara on a collision course with the very companies that have deprived her of her freedom. Eerie, urgent, and ceaselessly clear-eyed, The Dream Hotel artfully explores the seductive nature of technology, which puts us in shackles even as it makes our lives easier. Lalami asks how much of ourselves must remain private if we are to remain free, and whether even the most invasive forms of surveillance can ever capture who we really are.